2001
DOI: 10.1021/jp0035941
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of Large-Amplitude Side Chain Motions to the Excited-State H-Atom Transfer of Perylene Quinones:  Application of Theory and Experiment to Calphostin C

Abstract: The excited-state intramolecular H-atom transfer reactions of hypocrellins B and A are compared with those of calphostin C. On the basis of the results of transient absorption measurements and ab initio quantum mechanical calculations, it is concluded that large-amplitude conformational changes are coupled to the Hatom transfer in calphostin C, just as they are in hypocrellins A and B. The calculations on this very large molecule with a very complex ground electronic state potential energy surface were made po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…And the height of the barrier between the two minima is 1.70 kcal/mol. These results are consistent with the prediction of Petrich et al [18,19] that a barrier exists for the intramolecular proton transfer in hypocrellin A which has seven-member ring.…”
Section: Dhnq and Dhpsupporting
confidence: 93%
See 1 more Smart Citation
“…And the height of the barrier between the two minima is 1.70 kcal/mol. These results are consistent with the prediction of Petrich et al [18,19] that a barrier exists for the intramolecular proton transfer in hypocrellin A which has seven-member ring.…”
Section: Dhnq and Dhpsupporting
confidence: 93%
“…Recent studies in experimental and theoretical points of view [14][15][16][17] have abandoned such a double minimum potential, but proposed a single minimum potential for the S 0 and S 1 state and the ESIPT process with no barrier in the S 1 state. However, Petrich et al [5,18,19] recently reported the fluorescence up-conversion measurements of hypericin and hypocrellin A in a variety of solvents. Hypericin executes ESIPT in $10 ps and is independent of solvent, on the other hand, the H-atom transfer time for hypocrellin A in ethanol and octanol is range from 50 to 100 ps.…”
Section: Introductionmentioning
confidence: 99%
“…We propose that it is the time scale for this latter conformational change that determines the observed H-atom transfer time. The exact nature of the conformational changes that are coupled to the H-atom transfer reaction in hypericin and hypocrellin has yet to be identified (54).…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Fig. 1, the required EDAHB was synthesized using methods described in our previous article (4 Investigations of the intramolecular proton transfer process in perylenequinone pigments have suggested that the intramolecular H-atom transfer process might play a significant role in photodynamic therapy (5)(6)(7)(8)(9)(10). To study this process further, we synthesized monomethylated (MMHB) and dimethylated HB (DMHB) as described in our previous article (as shown in Fig.…”
mentioning
confidence: 99%